2019
DOI: 10.1177/1076029619826317
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Efficacy of Age-Adjusted D-Dimer Cutoff Value and Pretest Probability Scores for Deep Venous Thrombosis

Abstract: This study seeks to evaluate the diagnostic value of D-Dimer Plus and Innovance D-Dimer as well as the age-adjusted cutoff value for D-dimer detection in combination with 4 pretest probability (PTP) scores for deep venous thrombosis (DVT). A total of 688 patients referred for lower extremity vascular compression venous ultrasonography for suspected DVT from January 2016 to May 2018 in the First Affiliated Hospital of Sun Yat-sen University underwent D-dimer tests combining with 4 PTP scores. The diagnostic eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…Some studies showed that the use of age-adjusted D-dimer cut-off in the diagnostic strategy for the specificity and sensitivity of deep vein thrombosis is more valuable over 50 years old [ 7 , 8 ]. Nybo and Hvas argued that the use of an age-adjusted D-dimer in patients above 50 years of age for ruling out DVT seems as safe as using a standard D-dimer cut-off [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies showed that the use of age-adjusted D-dimer cut-off in the diagnostic strategy for the specificity and sensitivity of deep vein thrombosis is more valuable over 50 years old [ 7 , 8 ]. Nybo and Hvas argued that the use of an age-adjusted D-dimer in patients above 50 years of age for ruling out DVT seems as safe as using a standard D-dimer cut-off [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Each variables is strongly associated with DVT in trauma patients. It has previously [23] been described that the D-dimer could further improve both the speci city and the positive predictive value based on age-adjusted cutoff values; therefore, it is not surprising that this was incorporated into our predictive model. The risk factor of ISS has been validated as an independent risk factor for DVT diagnosis, and the incidence of DVT signi cantly increases with increasing ISS trauma score [24].…”
Section: Discussionmentioning
confidence: 93%
“…When employing D-dimer, many studies have taken various measures to improve the diagnostic value of D-dimer. 23 , 31 , 32 Ke et al used a respective cut-off value of D-dimer in subgroups and elevated the diagnostic ability of D-dimer in lung cancer patients after surgery. 23 In the present study, we performed a separate ROC analysis in order to determine the cut-off value in subgroups.…”
Section: Discussionmentioning
confidence: 99%